2018
DOI: 10.1093/cid/ciy171
|View full text |Cite
|
Sign up to set email alerts
|

Bezlotoxumab for Prevention of Recurrent Clostridium difficile Infection in Patients at Increased Risk for Recurrence

Abstract: BackgroundBezlotoxumab is a human monoclonal antibody against Clostridium difficile toxin B indicated to prevent C. difficile infection (CDI) recurrence (rCDI) in adults at high risk for rCDI. This post hoc analysis of pooled monocolonal antibodies for C.difficile therapy (MODIFY) I/II data assessed bezlotoxumab efficacy in participants with characteristics associated with increased risk for rCDI.MethodsThe analysis population was the modified intent-to-treat population who received bezlotoxumab or placebo (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
145
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 157 publications
(154 citation statements)
references
References 22 publications
7
145
1
1
Order By: Relevance
“…Patients with more than or equal to three risk factors experienced the greatest reduction in CDI recurrence with BEZ (− 24.8% [range − 39.1%, − 9.3%]), suggesting a potential targeted patient population for the drug. One limitation of these data is that several of the risk factors are loosely defined, including immunocompromised patients, which was based on clinical criteria [21]. …”
Section: Discussionmentioning
confidence: 99%
“…Patients with more than or equal to three risk factors experienced the greatest reduction in CDI recurrence with BEZ (− 24.8% [range − 39.1%, − 9.3%]), suggesting a potential targeted patient population for the drug. One limitation of these data is that several of the risk factors are loosely defined, including immunocompromised patients, which was based on clinical criteria [21]. …”
Section: Discussionmentioning
confidence: 99%
“…The patients to be selected are obviously those in whom a high risk of recurrence is predictable. In this sense, the best-known elements of risk associated to the host are advanced age (≥65 years), the need to maintain antibiotic treatment for baseline infection, deficiencies in humoral immunity response, serious underlying diseases and the need to continue taking proton pump inhibitors, among others [185]. As the microorganism is concern, it seems clear that strains with high toxin production, as is the case with many of those grouped as 027, are associated with an increased risk of recurrence [186][187][188][189].…”
Section: Question 9 When and How To Report Clinicians The Results Ofmentioning
confidence: 99%
“…Interestingly, these scoring systems show us that certain patients in the first episode of CDI have a higher risk of recurrence than other patients in the second episode [185].…”
Section: Question 9 When and How To Report Clinicians The Results Ofmentioning
confidence: 99%
“…The addition of actoxumab (human monoclonal antibody against CD toxin A) did not result in enhanced effectiveness of bezlotoxumab 7 . After additional analysis of aggregatedata from MODIFY I and II studies, based on stratification of risk for recurrence, bezlotoxumab showed not onlysignificant reduction of recurrent events, but also FMT was used to a lesser degree and lower readmission rate to hospital at 30 days due to CDI was registered in comparison to placebo 20 . Taking into account the latter results, it was recommended that patients who have 3 or more risk factors for recurrent CDI can benefit most from adding bezlotoxumab to standard antibiotic treatment, and this could also be useful for those with fewer risk factors 20 .…”
Section: Bezlotoxumabmentioning
confidence: 99%
“…After additional analysis of aggregatedata from MODIFY I and II studies, based on stratification of risk for recurrence, bezlotoxumab showed not onlysignificant reduction of recurrent events, but also FMT was used to a lesser degree and lower readmission rate to hospital at 30 days due to CDI was registered in comparison to placebo 20 . Taking into account the latter results, it was recommended that patients who have 3 or more risk factors for recurrent CDI can benefit most from adding bezlotoxumab to standard antibiotic treatment, and this could also be useful for those with fewer risk factors 20 . However, this shortlived protective effect of bezlotoxumab requires further investigations that would deal with its possible long-term positive influence on incidence of recurrent CDIs.…”
Section: Bezlotoxumabmentioning
confidence: 99%